Zoing agroclimatological Coffea canephora for Espírito Santo by spatial interpolation - Eugenio, Fernando Coelho; Peluzio, Telma Machado de Oliveira; Pereira, Ana Aparecida Barbosa; Santos, Alexandre Rosa dos; Peluzio, Joao Batista Esteves; Bragança, Rosembergue; Fiedler, Nilton César; Paula, Elizabeth Neire da Silva Oliveira de (Coffee Science - ISSN 1984-3909, 2014)
This study aims to propose the determination of the Zoning Agroclimatological Coffea canephora by using spatial reclassification percentages of classes for the state of Espírito Santo. The methodological steps needed to assess the relationship of zoning agroclimatological to the culture of Coffea canephora, were generating the database and multiple linear regression; spatial interpolation by kriging spherical; reclassification and zoning agroclimatological; vectorization spatial zoning and zoning quantification agroclimatological for 78 municipalities in the state. The results showed that the state of Espírito Santo has areas full (100%), good (75%), fair (50%), restricted (25%) and totally inapt to the cultivation of coffee conilon, representing, respectively, 6.92 %, 24.47%, 37.40% and 0.97% of the territory. The methodology of spatial reclassification percentages classes was efficient.